Academy and Post-industrial Journalism. From Massive Culture to Dismassification and Fragmentation - Mazzone, Daniel (2013)
In the academic careers of subfields like Journalism, the communicational field is at a crisis caused by the gap between theory accumulation and knowledge reproduction. Thirty years ago, Verón and Martín-Barbero proposed a new approach, displacing analysis of the media to mediations. In 2008, Scolari started focusing in the hypermediations, consisting of forwards, hybridization and contaminations. In 2009, Castells put emphasis on the observation of social transformations provoked by mass auto-communication. While we must think in dismassification and fragmentation, obsolete notions like massive culture or cultural industry resist, reducing the profession to a poor monologue with little incidence in the informative management. The subject of this paper is to discuss the factors that disturb the connection between two academic plans necessarily interdependent.